Does Leadership on the Field Get You Noticed Off It?: The Value of Varsity Sports to Corporate Recruiters - Tracy, Allison Joye; Erkut, Sumru; Pappano, Laura (Journal of Amateur Sport, 2020)
An online correspondence study was conducted to explore whether professional recruiters screening candidates for entry-level corporate jobs would view leadership skills acquired through high level participation in amateur sports at the collegiate varsity level more favorably than those acquired through non-sports activities. The experimental manipulation randomly varied candidates’ athletic v. non-athletic leadership experience at university, their gender, and race. Eight hundred and twenty-eight corporate recruiters rated four potential candidate profiles on four of eight job-relevant leadership traits/skills they valued most when assessing a candidate and ranked the candidates for a callback interview. Varsity athletes were rated higher than non-athletes on the ability to work in a team and on being results-driven. However, recruiters rated athletes lower in critical thinking, follow-through on tasks, and organizational skills. Overall, athletes were no more likely than non-athlete candidates to be selected for a first interview. Results are interpreted in the context of signaling theory.